MENANGKAL DESAKRALISASI DESTINASI WISATA PURA MELALUI REVITALISASI AJARAN PENDIDIKAN AGAMA HINDU - I Wayan Rudiarta; Puput Puspita Sari; Ni Wayan Ariani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
This research aims to describe the results of scientific study related to efforts to prevent the desacralization of temples as tourist destinations. This is based on the fact that there are many temples that have an attraction to be visited by domestic and foreign tourists. On the one hand, the adoption of temples as tourist destinations provides many advantages, especially from an economic perspective. However, irresponsible actions often occur by tourism actors, both managers and tourists themselves. Various cases of temple abuse occurred in Bali which indicated that there was an error in the management of temple tourist destinations. This research uses a qualitative approach with data collection in the form of literature review and technical analysis through data reduction, data display, and conclusion drawing. The results obtained from this study, that there are several temples in Lombok which are tourist destinations because they are unique in terms of history, place, and shape. The existence of the temple as a tourist destination has challenges in the the ethics of entering the temple which spiritually will affect the level of sanctity (sacred) of the temple. To anticipate this, it is necessary to revitalize the teachings of Hindu religious education to all tourism actors through the concepts of Tri Hita Karana, Tri Kaya Parisudha and Catur Paramita.Keyword: desacralization, temple, tourist destinations, Hindu religious education.